EMBRACING THE NEW GEN ED CURRICULUM: LIVED EXPERIENCES OF GE TEACHERS (Proceedings of the International Conference on Education, 2023)
The continuously changing educational landscape and the demands of 21st century education call for curricular reforms.  In the Philippines, the Commission on Higher Education (CHED) issued CHED Memo#20,s.2013 which revised the General Education curriculum in tertiary education and standardized its implementation. And in any changes in the curriculum, the roles and responsibilities of the teachers as curriculum implementers will have an impact in its successful implementation.  Given this premise, this phenomenological study looked into how the teachers implemented the New General Education curriculum (NGEC) in School Year 2021-2022, three years after its implementation in 2018. The study answered this central question: How do teachers describe their experiences in teaching the new GE curriculum and their perceived influence/effect of general education courses to the students?  The participants of this study were NGEC teachers for not less than 3 years. This phenomenological study is anchored on the Concerns-Based Adoption Model (CBAM) and employs thematic analysis. The themes emerged were the use of different teaching strategies, adaptability of the curriculum, enrichment of teachers’ personal values, cultivation of students’ soft skills and their application of concepts to daily life.  In conclusion, NGEC according to the participants has positive effects or impacts in their work as GE teachers and they perceive that it positively affects the values/skills gained by the students. The results of this study contribute to the field of curriculum implementation and assessment in as much as it attempts to know the experiences of curriculum implementers which will be useful for the revision and improvement of the GE curriculum.
Keywords: curriculum; General Education curriculum; curriculum implementation; phenomenological study